2014
DOI: 10.1128/jvi.02179-14
|View full text |Cite
|
Sign up to set email alerts
|

Specific Cells in the Primary Salivary Glands of the Whitefly Bemisia tabaci Control Retention and Transmission of Begomoviruses

Abstract: The majority of plant viruses are vectored by arthropods via persistent-circulative or noncirculative transmission. Previous studies have shown that specific binding sites for noncirculative viruses reside within the stylet or foregut of insect vectors, whereas the transmission mechanisms of circulative viruses remain ambiguous. Here we report the critical roles of whitefly primary salivary glands (PSGs) in the circulative transmission of two begomoviruses. The Middle East Asia Minor 1 (MEAM1) species of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
85
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 53 publications
3
85
0
2
Order By: Relevance
“…The study obtained 13,615 unigenes, among which several highly expressed genes with functions that might be involved in virus transmission or passage such as genes encoding for secretory proteins [73]. Recently, Wei et al [72 ] suggested that specific cells in the PSGs, the cells around the secretory regions are an important site that controls the specificity of TYLCV and TYLCCNV transmission. Localization of TYLCV in the midgut of Bemisia tabaci following acquisition of the virus from infected plants for several days.…”
Section: Mechanisms and Proteins Involved In Whitefly-begomovirus Intmentioning
confidence: 97%
See 1 more Smart Citation
“…The study obtained 13,615 unigenes, among which several highly expressed genes with functions that might be involved in virus transmission or passage such as genes encoding for secretory proteins [73]. Recently, Wei et al [72 ] suggested that specific cells in the PSGs, the cells around the secretory regions are an important site that controls the specificity of TYLCV and TYLCCNV transmission. Localization of TYLCV in the midgut of Bemisia tabaci following acquisition of the virus from infected plants for several days.…”
Section: Mechanisms and Proteins Involved In Whitefly-begomovirus Intmentioning
confidence: 97%
“…Those molecular changes were accompanied with suppressing immune responses in the whitefly by down regulating the expression of genes involved in Toll signaling and mitogen activated protein kinase (MAPK) pathways [71]. B. tabaci PSGs are a major organ in the transmission pathway of begomoviruses [72 ] ( Figure 1), and the transcriptome of the PSGs of MED B. tabaci was sequenced [73] for the possible identification of receptors or proteins involved in begomoviruses transmission. The study obtained 13,615 unigenes, among which several highly expressed genes with functions that might be involved in virus transmission or passage such as genes encoding for secretory proteins [73].…”
Section: Mechanisms and Proteins Involved In Whitefly-begomovirus Intmentioning
confidence: 99%
“…Experimental studies have shown that putative species of this complex differ in many aspects of their biology, such as host range (Zang et al ., ; Xu et al ., ; Sun et al ., ), resistance to insecticide (Wang et al ., ; Rao et al ., ; Horowitz & Ishaaya, ), behavior (Liu et al ., ; Crowder et al ., ; Luan & Liu, ; Wang et al . ; Luan et al ., ) and specificity of begomovirus transmission (Li et al ., ; Polston et al ., ; Wei et al ., , ). Thus recognition of the cryptic species in this whitefly complex is critical to meaningful biological research and effective management (Boykin et al ., ; De Barro, ; Boykin & De Barro, ).…”
Section: Introductionmentioning
confidence: 99%
“…Virions are subsequently transported through the hemocoel into the salivary glands and from there they are finally excreted with the saliva during feeding. 13,14 During the circulative transmission of begomoviruses, viral particles interact with various whitefly proteins. 15,16 As demonstrated for tomato yellow leaf curl virus (TYLCV) which is a destructive pathogen of tomato crops, the whitefly GroEL protein seems to bind and protect TYLCV from degradation in the haemolymph.…”
Section: Introductionmentioning
confidence: 99%